Leveraging African language radio for public health education in South Africa: A case study of Umhlobo Wenene FM. - Onyenankeya, Kevin (Radio Journal: International Studies in Broadcast & Audio Media, 2026)
Public health awareness and education are critical in the health ecosystem of every country, specifically in promoting healthy living and managing public health crises. The main objective of this article was to investigate the public health promotion programming of Umhlobo Wenene FM (UWFM), exploring how the station located in the Eastern Cape Province of South Africa uses its flagship programme, Khanya ku Khanye, to create public health awareness and advocate healthy living among its Xhosa-speaking listeners. Anchored within the audience reception and engagement theories, data for this study were collected using a combination of in-depth interviews and audio content analysis. The results show that UWFM's Khanya ku Khanye programme provides an important platform for listeners, especially the population in the margins, to access health information and express their perspectives on current public health issues. Because UWFM broadcasts in a language and format consistent with the audience's sociocultural, demographic and psychographic peculiarities, it can be a potent platform for creating public health awareness and participation in public health interventions, especially in rural areas.